Post-Secondary Education Development in South East Asia: A Model for Curriculum Development in Continuing Education - MacKinnon, Allan (Alberta Journal of Educational Research, 2013)
This article presents a model for continuing education that emanated from the author’s involvement in the Participatory Action Research (PAR) component of Simon Fraser University’s Adult Education for Economic Development (AEED) Project, funded by the Canadian International Development Agency (CIDA). The project’s goal was to develop new centers for continuing education at the Royal University of Phnom Penh (RUPP) in Cambodia and the National University of Laos (NUOL) in Lao People’s Democratic Republic, with assistance and mentorship from the Centre for Continuing Education at Chulalongkorn University (Chula) in Thailand. This article includes a discussion and illustration of continuing education based on four dimensions: lifelong learning, outreach, applied and integrated studies, and informal learning environments. The PAR is discussed in terms of how the partnerships emerged in the project, together with a systemic, ecological analysis of continuing education. Cet article présente un modèle d’éducation permanente qui est ressorti de l’implication de l’auteur dans la composante recherche-action participative du projet Adult Education for Economic Development (l’éducation des adultes pour le développement économique) de l’Université Simon Fraser financé par l’Agence canadienne de développement international. L’objectif du projet était de développer de nouveaux centres d’éducation permanente à l’Université royale de Phnom Penh au Cambodge et à la l’Université nationale du Laos à la République démocratique populaire lao, avec l’appui et le mentorat du centre pour l’éducation permanente à l’Université Chulalongkorn en Thaïlande. Cet article présente une discussion et une illustration de l’éducation permanente reposant sur quatre dimensions : l’apprentissage tout au long de la vie, la conscientisation ou le rapprochement, les études appliquées et intégrées, et les milieux d’apprentissage informels. La recherche-action participative est présentée en fonction de l’émergence des partenariats qui sous-tendent le projet et par le biais d’une analyse systémique et écologique de l’éducation permanente.